Resíduos nos ecossistemas costeiros e marinhos do Brasil: uma análise dos dados do projeto Blue Keepers - Mistro, Priscila (Universidade Federal de São Carlos, 2025)
Plastic waste pollution is one of the main threats to marine and coastal ecosystems, compromising biodiversity, marine fauna, and human quality of life. This study combines a literature review with the analysis of primary data collected between 2021 and 2024 by the Blue Keepers project, part of the UN Global Compact - Brazil Network, using tools such as Webmapa and the National Waste Inventory. The objective is to identify and classify the waste collected in the project's sample collections, map the main escape points (hotspots) of these materials into coastal and marine ecosystems, and assess their environmental impacts. The results reveal that plastics account for the largest share of the waste found, being particularly critical in mangrove, beach, and river areas. Additionally, the research highlights the need for effective public policies and initiatives in waste management and marine pollution mitigation. The conclusion emphasizes that environmental awareness and improved waste management strategies are essential to reducing negative impacts on the oceans and promoting sustainable development aligned with the Sustainable Development Goals (SDGs).
Waste in Brazil's coastal and marine ecosystem: an analysis of data from the Blue Keepers project
Keywords: Poluição marinha por plásticos; Impactos ambientais; Projeto blue keepers; Gestão de resíduos; Ecossistemas marinhos e costeiros; Blue keepers projects; Environmental impacts; Marine plastic pollution; Waste management; Marine and coastal ecosystems; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS; 12. Consumo e Produção Responsáveis